Deformation and wear map of DLC coating under cyclic impacts - Abdollah, Mohd Fadzli bin; Yamaguchi, Y.; Akao, T.; Inayoshi, N.; Miyamoto , N.; Tokoroyama, Takayuki; Umehara, Noritsugu (2011)
Generally, the construction of transition maps follow two different approaches ; empirical and physical modelling. However, only empirical approach is used in this study. In this century, there is no development of deformation-wear transition map of the DC coating under cyclic impact loading. Therefore, the aim of this study is to propose a new deformation-wear transition map of DLC coating based on variations of maximum normal impact loads and impact cycles for future design purposes.